Evaluation of renal arteries in hypertensive patients by multi-detector computed tomography - Sharma, Pradip; Singh, Sushma; Sharma, Saroj; Yadav, Rajesh Prasad; Shrestha, Avinesh; Sah, Suraj; Panta, Pratibha; Sapkota, Rabina (Journal of Gandaki Medical College-Nepal, 2023)
Introduction: Among various causes of hypertension, only 1 to 2% is renovascular hypertension which may be characterized by the various reasons in renal vascular supply. Multi-detector computed tomography is used to know about the details of the vascular structures in patients. This study aims to evaluate the renal arteries in hypertensive patients.Methods: A prospective observational study was conducted among 93 hypertensive patients. Contrastenhanced computed tomography of the abdomen and pelvis was conducted, and measurements were obtained from the axial section of the maximum intensity projection image. Data were analyzed using SPSS version 23.0. Independent t-test and Pearson’s Correlation were used. The level of statistical significance was set at p